Resistance to thyroid hormone due to a novel THRB p.Val349Ala mutation in a Taiwanese boy - Zhen Liu; Wen-Yu Tsai; Cheng-Ting Lee (Journal of the Formosan Medical Association, 2020)
Resistance to thyroid hormone (RTH) is a rare congenital disorder characterized by impaired sensitivity of target tissues to thyroid hormone. The disease is mostly caused by heterozygous mutations of thyroid hormone receptor β (THRB) gene. We present a ten-year-old Taiwanese boy with goiter, mood disturbances and attention deficit hyperactivity disorder (ADHD). Blood tests showed elevated serum thyroxine (T4) and triiodothyronine (T3) levels with nonsuppressed thyrotropin (TSH) levels. Sella MRI failed to detect any pituitary adenoma. Initial treatment with anti-thyroid drugs resulted in increased TSH levels and goiter size. His medication was discontinued after his visit to our hospital for a second opinion. A thyrotropin-releasing hormone (TRH) stimulation test showed a normal TSH response to TRH stimulation. Molecular analysis identified a novel heterozygous THRB p.Val349Ala mutation. The patient attained normal growth and a paucity of symptoms without any medication during the follow-up period. We hope that the presentation of this case can make the early diagnosis of RTH possible so that inappropriate management of these patients can be avoided in the future.